Understanding lifestyle sports : consumption, identity, and difference - Wheaton, Belinda, 1966- (Routledge critical studies in sport., 2004)
This collection of innovative studies represents the first serious academic investigation of 'lifestyle' or 'postmodern' sports, such as snowboarding, skateboarding and surfing.